The human rights approach and the protection of vulnerable groups in the migration policy and the legal order of peruvian state - Rodríguez Campos, Rafael (2019)
This article presents some institutional, doctrinal, normative and jurisprudential notes about the incorporation of the Human Rights Approach and the Protection of Vulnerable Groups, in the Migration Policy and the Legal Order in Peru; a reflection on the duty of the Peruvian State to adapt the legal system to human rights; and finally report the presence of the Human Rights Approach and the Protection of Vulnerable Groups in the actions implemented by the National Superintendence of Migration, also referring a particular mention on migrant children and adolescents as a Vulnerable Group which requires special protection.